THE IMPACT OF WORK MOTIVATION, ADDITIONAL INCOME ALLOWANCES AND ORGANIZATIONAL COMMITMENT ON THE PERFORMANCE OF SECTOR POLICE MEMBERS IN SABU RAIJUA REGENCY - Muslikhan A. Sara; Cosmas Fernandez; Jou Sewa Adrianus; Stefanie Noviega Bribin Burin (SEAN Institute, 2023)
The aim of this research is to determine whether there is an influence of Motivation (XI), Additional Income Allowance (X2) and Organizational Commitment (X3) on the Performance (Y) of Sector Police Members in Sabu Raijua Regency. The sample for this research was 64 members of the Sector Police in Sabu Raijua Regency. The method used in this research is a quantitative method with multiple linear regression analysis techniques use SPSS Version 26 Software. The data used is secondary data and primary data, hypothesis testing uses the coefficient of determination test (R²), t test and F test. The results of this research are Work motivation (X1) has a positive and insignificant effect on performance, Additional Income Allowances (X2) and Organizational Commitment (X3) have a positive and significant effect on Performance (Y) and the three variables X1, X2 and X3 simultaneously influence police performance.